COVID-19’s Impact on Bangladesh Economy - Siddiquee, Muhammad Shahadat Hossain; Faruk, Avinno (BRAC Institute of Governance and Development (BIGD), 2022)
This BIGD study examines the impact of COVID-19’s impact on the major economic and financial indicators of the economy of Bangladesh, including production, wages, price levels, advances, bills, investments, remittances and foreign trade, using the secondary data published by the Bangladesh Bureau of Statistics (BBS), Bangladesh Bank (BB), and the Ministry of Finance (MoF). In addition to the recent impact of the global economic meltdown, Bangladesh also experienced severe demand contraction in the local economy; this exacerbated the overall economic crisis of the country. Considering the duration and severity of COVID-19, we examine its impact on major economic and financial indicators of the Bangladesh economy and recommended policy responses for recovery, based on the analysis. Both domestic and international demands declined due to the outbreak and subsequent lockdown, and, thus, producers responded by lowering output to minimize the loss, especially in the manufacturing sectors. Findings reveal that nominal Wage Rate Index (WRI) in the industry and service sectors fell in recent times, which now appear to be recovering. The national inflation rate has not been affected much based on point-to-point changes. Food inflation fell in May 2020 and stood at 5.09 percent, but it appears to have risen recently. Non-food inflation rates have been falling over the last six months from April-September 2020. Prudent measures should include constant monitoring and adapting to the latest developments in major trading partners and host countries to mitigate the economic losses caused. Bank credit would play a key role in the ongoing and upcoming recovery process, as the government has opted for a credit-led stimulus package. However, as the virus is yet to be contained and an effective vaccine for it is yet to be made available in Bangladesh everywhere and to everyone, its economic repercussions are likely to continue in the foreseeable future.